Events below the Surface: A Reading of Henning Mankell’s The Troubled Man - John Lingard (Scandinavian-Canadian Studies, 2020)
ABSTRACT: Den orolige mannen (2009) [The Troubled Man, 2011] is Henning Mankell’s twelfth and last Kurt Wallander novel. Uniquely in the series, it combines detective and spy fiction. Its rich metaphoric texture is based on a continued play between surface and depth, between what is illusory and what is true. Wallander’s investigation into the disappearance of an aristocratic former naval officer, Håkan von Enke, and the death of that officer’s wife Louise, takes the detective back into the Cold War with its atmosphere of spies, moles, and treachery. Mankell also offers readers an unprecedented look into Wallander’s inner life where increasing moments of forgetfulness are leading him towards “det tomma universum som heter Alzheimer” [the empty universe that is called Alzheimer’s] (555). The novel is further enhanced by a metafictional retrospect of Wallander’s earlier career and his most important relationships: with his daughter Linda and the love of his life, Baiba Liepa.